Konsep al-Ashîl dan al-Dakhîl dalam Tafsir Alquran - Ulinuha, Muhammad (Madania: Jurnal Kajian Keislaman, 2017)
The Concept of al-Ashîl and al-Dakhîl in the Quranic Exegesis. This study examined the concept of al-ashîl and al-dakhîl in the Quranic exegesis. These two issues were important to discuss because in the books of exegesis there were many data and information that were irrelevant to the content of verses and sublime messages of the Quran. Even authoritative exegesis books were also not sterile from the infiltration of interpretation, either in the form of historical data, ra’y (the result of ijtihad) or inner cues. Based on this, this study aimed to explain the concept of ashâlat al-mashdar (source authenticity) so that al-dakhîl fî al-tafsîr (infiltration of interpretation) could be known, criticized and evaluated. Criticism of the infiltration of quranic interpretation was necessary so that the exegesis books—as a work in direct contact with the main source of Islam—were completely cleansed from the reality of al-dakhîl.